HUBUNGAN REWARD DAN PUNISHMENT DENGAN DISIPLIN KERJA PADA KARYAWAN RUMAH SAKIT GRANDMED LUBUK PAKAM KABUPATEN DELI SERDANG - Arif Sujatmiko; Rahmad Gurusinga; Iskandar Markus Sembiring; Novita Br Ginting Munthe; Indah Pratiwi (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2020)
Grandmed Lubuk Pakam Hospital applies reward and punishment in completing employee work discipline that must be in accordance with hospital regulations. Good rewards and punishments can motivate employees to improve work discipline and help employees achieve effective performance. This study aims to determine the Relationship of Reward and Punishment with Work Discipline in Employees of the Grandmed Lubuk Pakam Hospital in 2020. This type of quantitative research is analytic survey using cross sectional design. The sample in this study was taken by purposive sampling of 48 employees. Analysis using the Chi-Square test with a confidence level of 95%, Î± = 0.05. The results of the research between reward and work discipline show that there is a significant relationship between reward and work discipline in the employees of Grandmed Lubuk Pakam Hospital in 2020, p value (0.022) <Î± (0.05) is obtained. While the results of research between punishment with work discipline that shows there is a significant relationship between punishment with work discipline on employees of the Grandmed Lubuk Pakam Hospital in 2020. From the Chi Square test results obtained p value (0.036) <Î± (0.05). It is expected that the hospital should pay more attention to the rewards and punishments for employees to further improve discipline, work motivation, work morale so that they can be maintained or further improved and it is advisable to pay more attention to work discipline to employees by giving reprimands or punishment to employees who work discipline is not good so the bias is even better.